Synthèse et étude de l’interaction des quelques hydrazides ferrocéniques avec l’anion radical superoxyde, le DPPH et l’ADN - MOUADA Hanane; LANEZ Touhami (University Of Eloued جامعة الوادي, 2020)
In the present work, we report the synthesis and characterization of N’ ferrocenylmethyl N’ phenylalcane (or benzo) hydrazides by the treatment of the ferrocenyl methyl trimethyl ammonium iodide with N’phenylalcan (or benzo) hydrazides and the evaluation of the antioxidant and antitumor act ivities in a precise and modern technics technics. The antioxidant activity of our synthesized derivatives (FhD) against superoxide anion and 1,1 diphenyl 2picrylhydrazyl radicals were evaluated using electrochemical (CV) and Spectrometric (Uv visible spectroscopy) methods and binding parameters were calculated from analysis data data. While the antitumor activity of FhD was evaluated from studying their interaction with deoxyribonucleic acid and the binding parameters such as binding constant, free binding energy, diffu sion coefficient, and binding site size were determined from electrochemical, spectrometric measurements and validated by molecular docking.
Intervention
Keywords: F errocene derivatives; cyclic voltammetry; DPPH; DNA; molecular